Ruang sosial dan keberlanjutan desa wisata - Chondro Suryono; Fitri Abdillah (Lentera Negeri, 2026)
Tourism village development is often associated with economic growth and increasing tourist arrivals, while the social dimensions supporting tourism governance and community cohesion remain underexplored. This study examines the functions of social space in supporting community-based tourism sustainability in Cibuntu Tourism Village. A qualitative descriptive approach with a single holistic case study was employed. Data were collected through semi-structured interviews with 10 participants selected using purposive and snowball sampling, complemented by direct observation and document analysis. Data were analysed thematically, with credibility enhanced through triangulation, member checking, and extended field observation. The findings identify five interconnected functions of social space: community welfare, participatory governance, conflict resolution, tourism benefit sharing, and tourism experience. These functions are reflected in collective acceptance of the closure of sand mining and relocation of sheep enclosures through deliberation, a homestay guest-allocation system to distribute tourism opportunities, and meaningful interactions between residents and tourists. The findings demonstrate that social space functions not merely as an arena of interaction but as a relational mechanism that strengthens social solidarity, trust, participation, social legitimacy, benefit sharing, and harmonious stakeholder relationships. Thus, the sustainability of Cibuntu Tourism Village depends not only on its tourism resources but also on the community's capacity to maintain and reproduce its social space amid tourism development.